(untitled) (Brazilian Journal of Oceanography, 2004)
In order to determine the sedimentological and physico-chemical characteristics of the benthic environment and also the level, distribution and probable sources of aliphatic and polycyclic aromatic hydrocarbons, sediment samples were collected at 28 stations in the northeast portion of Todos os Santos Bay. The centre and the east region of the study area showed characteristics of depositional environments with the predominance of silt and clay and high percentages of TOC, nitrogen and sulphur. The molar C/N ratios varied between 8.8 and 27.6 indicating a mixed origin of organic matter with variable marine and continental contributions. Total aliphatic hydrocarbon concentrations ranged between 1.56 and 246.91 µg.g-1 dry weight, corresponding the high concentrations to the stations situated in the centre and in the east region of the study area. The UCM represented between 60 and 96% of the total aliphatic hydrocarbons, indicating a high degree of anthropogenic contribution and the presence of petroleum degraded residues. Total PAH concentrations varied from 8 to 4163 ng.g-1 dry weight. The highest total PAH concentration was recorded at station 5 situated adjacent to the oil refinery.